Conceptualising personal resources on career adaptability - Khoo, Kai Le; Hamzah, Siti Raba'ah; Omar, Zoharah (Human Resource Management Academic Research Society, 2019)
The literature on career adaptation is vast and based on a range of different measurement approaches. The present paper aims to understand the influence of personal resources on career adaptability in terms of concern, control, curiosity, and confidence among graduates. This study is based on an extensive review of past research on personal resources and career adaptability using the career construction theory. To conduct the literature review, we used keywords such as personal resources, emotional intelligence, self-esteem, self-efficacy, and career adaptability. From the literature reviewed, three predictors of career adaptability have been identified. They are emotional intelligence, self-esteem, and self-efficacy. The framework offers a number of propositions, which explain the proposed model of career adaptability among the graduates as predicted by personal resources. Further research is suggested to test and validate the framework provide empirical evidence. Upon model validation, the paper could offer stakeholders to assist and develop graduates’ personal resources in order to increases their career adaptability and then successful in their career path.